(COMPENSATION FOR REMAINING LAND IN THE CONSTRUCTION OF THE BAKAUHENI-TERBANGGI BESAR TOLL ROAD; DUE TO LAWS AND LAND CONFLICTS) - Andriawan Kusuma (Universitas Lampung, 2019)
The development of the Trans Sumatera toll road for the Bakauheni-Terbanggi Besar Section II package currently causes uncertainty in the calculation of compensation for residual lands, so that there is a change in the function of the land from the remaining land affected by the development. The remaining land referred to in this study is the rest of the land that has been compensated by agencies that need land, in this case the Ministry of Public Works and Public Housing but still leaves problems that have not been resolved. The problem in this study relates to the basis and process of settlement of compensation for the residual land that has lost its social function and economic value in the construction of the JTTS Bakauheni-Terbanggi Besar Section, efforts that must be undertaken by the community for the remaining land that loses social function and economic value in the JTTS development Large Bakauheni-Terbanggi Section. This research is a normative and empirical juridical research. This research was conducted in Serdang Village, tanjung Bintang District, South Lampung Regency. Aiming. This study uses a normative legal problem approach (library research). The results of this study indicate that the remaining land can be classified based on its designation, namely, agriculture / plantation, settlement and place of business which are categorized into 2 (two) based on the type of loss experienced by the rightful parties namely: economic losses and social losses. Where economic losses can be requested for compensation in the form of money while social losses can be given access roads to the remaining land so that the residual land that loses its social function will live and the economic value of the residual land will not decrease so that it will not suffer economic losses.